2016
DOI: 10.1111/mpp.12367
|View full text |Cite
|
Sign up to set email alerts
|

The fungal‐specific transcription factor Vdpf influences conidia production, melanized microsclerotia formation and pathogenicity in Verticillium dahliae

Abstract: Verticillium dahliae is a soil-borne, hemibiotrophic phytopathogenic fungus that causes wilting in crop plants. Here, we constructed a random insertional mutant library using Agrobacterium tumefaciens-mediated transformation to study the pathogenicity and regulatory mechanisms of V. dahliae. The fungal-specific transcription factor-encoding gene Vdpf was shown to be associated with vegetative growth and virulence, with the highest transcript expression occurring during conidia formation in the V991 strain. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 86 publications
(120 reference statements)
4
50
0
Order By: Relevance
“…S2D–F). It has been shown previously that Fungal_trans domain‐containing proteins are associated with vegetative growth in vitro in other pathogens (Jonkers et al ., ; Lu et al ., ; Luo et al ., ). Unexpectedly, the colony morphology of the VdFTF1‐ deletion mutants on PDA did not differ from the morphology of the wild‐type strain or the T‐DNA insertion mutant M06D06 on PDA.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…S2D–F). It has been shown previously that Fungal_trans domain‐containing proteins are associated with vegetative growth in vitro in other pathogens (Jonkers et al ., ; Lu et al ., ; Luo et al ., ). Unexpectedly, the colony morphology of the VdFTF1‐ deletion mutants on PDA did not differ from the morphology of the wild‐type strain or the T‐DNA insertion mutant M06D06 on PDA.…”
Section: Resultsmentioning
confidence: 97%
“…As our understanding of the pathogenicity of V. dahliae increases, it appears that a variety of genes are required for virulence towards host plants, including protein kinases (Rauyaree et al ., ; Tian et al ., ; Tzima et al ., ), TFs (Luo et al ., ; Santhanam et al ., ; Sarmiento‐Villamil et al ., ; Tran et al ., ; Xiong et al ., ), effectors (de Jonge et al ., ; Liu et al ., ; Santhanam et al ., ), enzymes involved in plant cell wall degradation (Chen et al ., ; Liu et al ., ; Maruthachalam et al ., ) and other functional genes (Gao et al ., ; Klimes and Dobinson, ; Li et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhang DD et al ., ; Zhang YL et al ., ). In this study, we identified a new pathogenicity and virulence‐related gene encoding a Fungal_trans domain‐containing TF (Figs and ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, TFs, through interaction with other TFs or molecular chaperones, play important roles in the virulence or pathogenicity of V. dahliae (Meshi and Iwabuchi, 1995;Pabo and Sauer, 1992). The fungal-specific TF Zn (II) 2 Cys 6 -type Vdpf plays important roles in melanized microsclerotia formation, conidia production and pathogenicity (Luo et al, 2016). RGSs act as GTPase accelerators that promote GTP hydrolysis by the Ga subunits, thereby inactivating the G protein and rapidly switching off G protein-coupled signalling pathways .…”
Section: Excavation Of the Virulence Gene In V Dahliaementioning
confidence: 99%